APPLICATION OF THE TAGUCHI METHOD IN AN EFFORT TO OPTIMIZE THE SHRIMP HEAD POWDER BROTH PRODUCTION PROCESS - siti nur kayatun; Muhammad Arief Nur Wahyudien; Mirga Maulana Rachmadhani; Asih Ahistasari; Arfandi Ahmad (Center for Study and Journal Management FTI UMI, 2023)
Indonesia is a maritime country with abundant marine resources. Currently, Indonesia is a country that exports marine products, one of which is shrimp. The shrimp exported are headless shrimp. One of the shrimp exporting cities is Sorong City, Southwest Papua Province. One shrimp export company is capable of producing and exporting 1,800 – 2,000 tons of shrimp per year. Therefore, this research focuses on good production processes to produce good products. This research applies the Taguchi method in the sample making process, and then carries out proximate analysis as product testing. The results of this research show that an experiment with a temperature of 200 and a time of 80 minutes is the best level which produces a product with the lowest air content and a protein content of 43.90%, fat 2.58% and carbohydrates 9.80%. This value is the best value of all levels